2016
DOI: 10.4236/eng.2016.87042
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Health Workers’ Perceptions on Medical Waste Management in Tanzanian Hospitals

Abstract: This paper presents the perceptions of health workers (HWs) on medical waste management (MWM) issues in Tanzanian hospitals. The perceived total waste generation rates were lower than the actual measurements. Administrators perceived lower rates than implementers. The results indicated three categories of medical waste which are given due attention, that is, sharps waste, pathological and infectious waste. Other wastes like radioactive, chemical, pharmaceutical, pressurized containers receive very little atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
1
9
1
Order By: Relevance
“… 30 The findings in the present study of all the doctors, intern doctors and sixth year medical students having knowledge on infectious diseases which are associated with lack of proper waste management in the present study, are in agreement with the results in Malini and Bala 21 and Ramokate and Basu 6 where all the categories of the health care workers had good knowledge about the infectious diseases associated with improper management of health care waste. The results on the lack of responses on the risks by the nurses and the cleaning staff are in agreement with the results of Kagonji and Manyele 29 where there was a low awareness among health care workers on the risks and diseases associated with poor management of health care waste.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“… 30 The findings in the present study of all the doctors, intern doctors and sixth year medical students having knowledge on infectious diseases which are associated with lack of proper waste management in the present study, are in agreement with the results in Malini and Bala 21 and Ramokate and Basu 6 where all the categories of the health care workers had good knowledge about the infectious diseases associated with improper management of health care waste. The results on the lack of responses on the risks by the nurses and the cleaning staff are in agreement with the results of Kagonji and Manyele 29 where there was a low awareness among health care workers on the risks and diseases associated with poor management of health care waste.…”
Section: Discussionsupporting
confidence: 88%
“…Pandit et al 28 and Saini et al 25 reported on much lower knowledge of the biomedical waste by the sanitary workers whereas in the present study there were higher numbers of cleaning staff who had knowledge on legislation and policy associated with healthcare waste management. In a study by Kagonji and Manyele 29 , the existence of crucial documents such as legislations, manuals and policies in all the surveyed hospitals was below 40.0% indicating that health care workers were not guided by any management tool which led to operating by intutuition hence leading to poor management of health care waste. The results on the knowledge and practises of participants regarding handling of the health care wastes are not comparable with findings of Debere et al 30 where none of the hospitals in the study reported using the colour coding system and there was also no segregation of health care waste.…”
Section: Discussionmentioning
confidence: 98%
“…erefore, it is imperative that sorting of hospital waste begins at the wards and units, using separate receptacles and different color codes for the infectious waste fractions, the sharps waste, and the noninfectious waste types and that adequate safeguards and labels for the high-risk waste are provided to prevent patients and hospital staff from contacting them. A study by [29] of two hospitals in Tanzania showed that at least 25% of medical waste in the two hospitals was not sorted at source. us, there was still a potential for disease infection at the wards and units and also at the storage points when sorted by waste handlers, as well as at disposal points by scavengers.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Tanzanian hospitals had concluded with findings that administrators perceived lower rates than implementers. [ 30 ] Individuals from urban areas have about 3 times higher odds of increased perceived risk than from rural areas. On the other hand, people living around the hospitals have 2.5 times higher odds of increased perceived risk than those people living near to health centers in a study done among community residents living around the hospital.…”
Section: Discussionmentioning
confidence: 99%